Supreme Audit Institutions Assessing Governments' Action. Worldwide and in Finland: Roots of Sustainable Development. - Niemenmaa, Vivi; Lähteenoja, Satu; Schmidt-Thom, Kaisa (Steiner, 2021)
Finland is one of the frontrunners in sustainable development policies globally. Government has a key role especially in integrating sustainability to the national budget. Government external auditors call for better policy coherence and long-term approach.
Keywords: Nachhaltige Stadtentwicklung; Entwicklungsziel; Umsetzung; Monitoring; Audit; Internationaler Vergleich; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung